2020
DOI: 10.1002/lpor.201900396
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced 2 µm Mid‐Infrared Laser Output from Tm3+‐Activated Glass Ceramic Microcavities

Abstract: Transparent glass ceramics (GCs) consisting of an homogeneous glass phase and a well-dispersed crystal phase are considered as ideal optical gain materials potentially applied in optoelectronic devices due to the combination of facile processability of glass and the intense crystal field of nanocrystals. Here, a heat-induced nanocrystal-in-glass method is employed to integrate the active ions Tm 3+ into Bi 2 Te 4 O 11 nanocrystals with an intense crystal field to realize an enhanced microlaser output. This str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…[ 34 ] Under 358 nm excitation, the GC–Tm/Cr sample also exhibits two emission peaks locating at 454 nm ( 1 D 2 → 3 F 4 ) and 480 nm ( 1 G 4 → 3 H 6 ), respectively (Figure 5b). [ 35,36 ] A sharp excitation peak at 358 nm was also observed monitoring at 454 nm. [ 37 ] Therefore, the ultraviolet and green light that are useless to photosynthesis can be converted into the red and blue emission regions simultaneously and reabsorption by photosynthetic pigment.…”
Section: Resultsmentioning
confidence: 98%
“…[ 34 ] Under 358 nm excitation, the GC–Tm/Cr sample also exhibits two emission peaks locating at 454 nm ( 1 D 2 → 3 F 4 ) and 480 nm ( 1 G 4 → 3 H 6 ), respectively (Figure 5b). [ 35,36 ] A sharp excitation peak at 358 nm was also observed monitoring at 454 nm. [ 37 ] Therefore, the ultraviolet and green light that are useless to photosynthesis can be converted into the red and blue emission regions simultaneously and reabsorption by photosynthetic pigment.…”
Section: Resultsmentioning
confidence: 98%
“…It has been demonstrated that the optical performance of active centers is strongly affected by the coordination environment. The photoluminescence efficiency can be significantly improved when the active centers transfer from an amorphous glass host to a crystal with low phonon energy 14–17 . Therefore, glass–ceramic (GC), especially oxyfluoride GC, which combines the merits of the excellent fiber‐drawing ability of glass host and prominent optical properties of fluoride nanocrystal, is considered an ideal candidate for the development of high‐performance fiber laser devices 18–21 .…”
Section: Introductionmentioning
confidence: 99%
“…The photoluminescence efficiency can be significantly improved when the active centers transfer from an amorphous glass host to a crystal with low phonon energy. [14][15][16][17] Therefore, glass-ceramic (GC), especially oxyfluoride GC, which combines the merits of the excellent fiber-drawing ability of glass host and prominent optical properties of fluoride nanocrystal, is considered an ideal candidate for the development of high-performance fiber laser devices. [18][19][20][21] During the crystallization process, the as-prepared glass (AG) is heat-treated around the onset crystallization temperature to facilitate the in situ precipitation of nanocrystals and a selective entry of active ions into crystalline lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The emission efficiency can be remarkably enhanced when the active ions move from a disordered amorphous glass matrix to an ordered rigid crystalline host due to the surpression of nonradiative decay process. [ 17–19 ] Therefore, a glass‐ceramic (GC) strategy combining the advantages of excellent fiber‐drawing ability of glass matrix and superior optical performance of nanocrystal has appear to be an ideal choice for the development of high‐performance optical fiber devices. [ 20–22 ] However, the widely used rod‐in‐tube method for the fabrication of glass optical fibers is not amenable to process low loss glass ceramic fibers (GCF).…”
Section: Introductionmentioning
confidence: 99%